Analisa Pembelajaran Bilingual Bagi Siswa Sekolah Dasar di Indonesia - Wildan, Risya Faiza Rizqi; Syafira, Alfina; Khoirunisa, Nur Salsa; Baodin, Nur Adila Binti; Septianto, Andhika Bagas; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the implementation of bilingual learning in Indonesian primary schools, focusing on the use of learning videos as instructional media. A qualitative approach with a case study method was employed to explore the strategies, models, and media used in bilingual instruction. Data were collected through observation and analysis of bilingual learning videos. The results indicate that bilingual learning positively impacts students' vocabulary acquisition and critical thinking skills. However, several challenges were identified, including low student participation, limited understanding of English vocabulary, and teachers' difficulties in balancing the use of Indonesian and English. The study also reveals that various teaching approaches were applied, such as cooperative learning, experiential learning, and problem-based learning. The instructional methods and media varied as well, including the use of videos, music, worksheets, and visual aids. Based on these findings, this research recommends the development of more interactive learning strategies, enhancing teachers' bilingual teaching skills, and providing more creative learning media to support effective bilingual learning in primary schools.